Pengaruh Metode Pengajaran Tanya Jawab Oleh Yesus Dalam Yohanes 4:1-28 Terhadap Keaktifan Belajar Pendidikan Agama Kristen Siswa Kelas VIII SMP Negeri 4 Tarutung TP 2023/2024 - Ester Gratia Siregar; Roida Lumbantobing; Goklas J. Manalu; Limmarten Simatupang; Masniar Sitorus (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The purpose of this research is to find out how much influence the question and answer teaching method used by Jesus in John 4:1-28 has on the learning activity of Christian Religious Education for Class VIII Students of SMP Negeri 4 Tarutung TP 2023/2024, with the hypothesis that there is a positive and significant influence from the method. teaching questions and answers by Jesus in John 4:1-28 on the active learning of Christian Religious Education for Class VIII Students of SMP Negeri 4 Tarutung TP 2023/2024. This research is a population study, namely all 99 students. Data was collected using a closed questionnaire with 45 items compiled by the author based on variable indicators according to the conclusions according to experts' theories. The questionnaire trial was carried out on 48 respondents of class VIII students at SMP Negeri 2 Tarutung using a 45-item questionnaire and after being tested, the results of the validity of the questionnaire trial showed that the value of rcount > rtable = 0.159-0.715 > 0.284 (there were 6 question items that had validity less than rtable = 0.284, namely item numbers 21, 25, 27, 34, 37, 44) and the reliability of the questionnaire trial was at a value of 0.939. It has been tested for validity and reliability. However, in research at SMP N 4 Tarutung, invalid questionnaire items were replaced so that the research was carried out using a new questionnaire. The data analysis technique used is making a distribution table of respondents' answers based on alternative answers, making a distribution table of respondents' answers, looking for the correlation coefficient between X and Y by calculating the Product Moment correlation, testing the real level with the t test, knowing the degree of influence of variable test the hypothesis with the t test. This research concludes that there is a positive and significant influence between the question and answer teaching method by Jesus in John 4:1-28 on the learning activity of Christian Religious Education students in class VIII of SMP Negeri 4 Tarutung TP 2023/2024 with the relationship test obtained rcount>rttable, namely 0.281> 0.195, with a significant test of the relationship between Tcount > Ttable, namely 2.875>1.985. This means that H0 is rejected and Ha is accepted.